2016
DOI: 10.1021/acs.est.6b03595
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Short- and Medium-Chain Chlorinated Paraffins (CPs) from a CP Production Plant to the Surrounding Surface Soils and Coniferous Leaves

Abstract: Chlorinated paraffin (CP) production is one important emission source for short- and medium-chain CPs (SCCPs and MCCPs) in the environment. In this study, 48 CP congener groups were measured in the surface soils and coniferous leaves collected from the inner and surrounding environment of a CP production plant that has been in operation for more than 30 years to investigate the dispersion and deposition behavior of SCCPs and MCCPs. The average concentrations of the sum of SCCPs and MCCPs in the in-plant conife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 35 publications
(50 reference statements)
4
19
1
Order By: Relevance
“…SCCP concentrations ranging from 69 to 1600 ng g −1 and 145 to 28.000 ng g −1 were determined in Kingtom and Agbogbloshie e-waste waste sites, respectively. Compared to literature data, the lowest SCCP concentration determined in the Agbogbloshie and Kingtom samples was similar to slightly higher than concentrations determined in ambient soils in China, UK and Norway (Xu et al 2016;Halse et al 2015). However, the highest SCCP concentration in Kingtom samples was similar to concentrations reported in farmland soils irrigated with wastewater and soils close to CP production plant (Zeng et al 2011a), whereas the highest concentrations determined in Agbogbloshie samples were similar to those recently published in China (Xu et al 2019b).…”
Section: Consumer Productssupporting
confidence: 84%
See 1 more Smart Citation
“…SCCP concentrations ranging from 69 to 1600 ng g −1 and 145 to 28.000 ng g −1 were determined in Kingtom and Agbogbloshie e-waste waste sites, respectively. Compared to literature data, the lowest SCCP concentration determined in the Agbogbloshie and Kingtom samples was similar to slightly higher than concentrations determined in ambient soils in China, UK and Norway (Xu et al 2016;Halse et al 2015). However, the highest SCCP concentration in Kingtom samples was similar to concentrations reported in farmland soils irrigated with wastewater and soils close to CP production plant (Zeng et al 2011a), whereas the highest concentrations determined in Agbogbloshie samples were similar to those recently published in China (Xu et al 2019b).…”
Section: Consumer Productssupporting
confidence: 84%
“…∑SCCP concentrations were detected at ND-5090 ng g −1 dw which indicated that CP production caused soil contamination of SCCPs. Only two studies were comparable with the obtained results (Xu et al 2016;Wang et al 2018b). The obtained results were also much higher than those reported by Bogdal et al (2017), Wang et al (2014) and Zeng et al (2011a).…”
Section: Sedimentsupporting
confidence: 79%
“…The concentrations of MCCPs and SCCPs in maize leaves herein were comparable to those in coniferous leaves obtained around another factory (MCCPs, 337.8−3711.1 ng/g dw and SCCPs, 218.7−1742.2 ng/g dw) and the SCCP levels in pine needles (11.8 μg g −1 lw), and they were an order of magnitude lower than those in mustard (148 μg g −1 lw and 291 μg g −1 lw on mean) sampled from a mega E-Waste recycling industrial park. 23,29 MCCPs were significantly higher than SCCPs (Friedman test, p < 0.05) in maize leaves. Results showed that the geometric mean concentration of MCCPs in maize leaves was about 2 times higher than those of SCCPs, which agrees roughly with the ratios of MCCPs/SCCPs of CP-52 products in China (1.6−8.2).…”
Section: Resultsmentioning
confidence: 84%
“…since sites 5 and 26 were located close to a small residential village and an agricultural path, respectively. 29,34,37 In addition, the nonhomogeneous diffusion of CPs from a manufacturing facility might be also one of the reasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation